Virtual Twelve Step Meeting Attendance During the COVID-19 Period: A Study of Members of Narcotics Anonymous. Issue 2 (15th March 2022) - Galanter, Marc; White, William L.; Hunter, Brooke
Abstract : Objectives: Face-to-face meetings are key components of Twelve Step (TS) fellowships' support of members' abstinence. Home confinement during COVID-19 made this less feasible. Our objective was to ascertain whether a transition to virtual online meetings among TS members took place, and whether it was potentially effective. Methods: Two thousand one hundred fifty-two long-standing USA members of Narcotics Anonymous (NA) were surveyed to ascertain their recovery-related experiences and their relation to the transition to virtual meetings. Results: During the previous week (ie, 'during COVID-19') respondents attended more virtual meetings (x ¯  = 4.13[SD4.64]) than they had attended both face-to-face meetings before COVID-19 (x ¯  = 3.35[SD2.05]), and also face-to-face meetings during COVID-19 (x ¯  = 0.75[SD1.8]). Many of the meetings were accessed from sites remote from their homes (44.4%), even overseas (21.5%). The majority (64.9%) found virtual meetings at least as effective in promoting their abstinence as were face-to-face meetings, and 41.8% estimated the same for newcomers. A shorter period of antecedent abstinence from drugs and increased loneliness were associated with increased craving during the transition period. Relative to Whites, Black respondents were less distressed, with a lesser increase in craving, and currently attended more virtual meetings. Data provided by a national program reflected a large increase in virtual TS attendance since the onset of the pandemic. Conclusions: In a survey of well-established NA members, most had made a successful transition from face-to-face to virtual meetings, relative to their antecedent characteristics. This successful transition suggests the possibility of an enhanced opportunity for stabilizing TS membership.